The effects of Ficus carica fruit on bone markers and oestrogen level of post-menopausal osteoporotic rats - Norfarah Izzaty R.; Nur Adlina M.; Mohd Dzulkhairi M.R.; Muhammad Shamsir M.A.; Nadia M.E. (International Islamic University Malaysia, 2024)
Introduction: Post-menopausal osteoporosis is the most common type of osteoporosis, which occurs due to a deficiency of oestrogen following menopause. Considering the adverse effects of oestrogen replacement therapy, natural products may serve to replace the current conventional treatment. Ficus carica (FC) which is commonly known as fig may have a potential in treating post-menopausal osteoporosis due to their abundance of important minerals and bioactive compounds such as phenolic, flavonoid and anthocyanins. This study aimed to evaluate the effects of FC on bone metabolism of ovariectomized rats. Materials and Methods: Fifty-six female Spraque-Dawley rats were randomly divided into seven groups; SHAM operated (SHAM), ovariectomized control (OVX), ovariectomized + 64.5 ?g/kg oestrogen (ERT), ovariectomized + 50 mg/kg aqueous extract of FC (AQ50), ovariectomized + 100 mg/kg aqueous extract of FC (AQ100), ovariectomized + 50 mg/kg raw FC (RW50), and ovariectomized + 100 mg/kg raw FC (RW100). After eight weeks of treatments, rats were euthanized and femurs were dissected out to measure bone osteocalcin, Ctelopeptide of type 1 collagen and bone estrogen level. Results: RW50 and RW100 showed an increasing trend in osteocalcin levels and also oestrogen level, but no significant difference between all groups. RW50 and RW100 also showed significantly reduced C-telopeptide of type 1 collagen levels compared to OVX group. Conclusion: These findings suggested that raw FC at the doses of 50 mg/kg and 100 mg/kg have potential to improve bone in treating post-menopausal osteoporosis. However, this need to be confirmed with higher doses. 2019 Default.